Características farmacognósticas de las hojas de alternanthera lanceolata (benth.) schinz “lancetilla” proveniente del distrito de Urpay provincia de Sánchez Carrión región La Libertad - Ramos Carrión, Marjory Rocio (2016)
Based on the biodiversity that exists in our country, medicinal plants have contributed as an essential resource to meet certain therapeutic and nutritional needs of many people. Furthermore, our country offers an almost unlimited potential of botanical material for pharmaceutical research. This study aims to determine the characteristics farmacognósticas leaves Alternanthera lanceolata (Benth.) Schinz "lancetilla" from the district Urpay.; province Sanchez Carrion region La Libertad I using the methodology of Miranda Migdalia Martinez, published in the article: "Analysis Method drug extracts and Dr. Migdalia Martinez Miranda" .It macromorphological evaluated the characteristics of the leaves, obtaining similarity with other species analyzed. It was determined the percentage of foreign matter, which is within the range established by WHO. Likewise, the phytochemical screening was performed; by Miranda Migdalia Martinez, where the possible presence of flavonoids, triterpenes and steroids, phenolics and tannins, catechins, saponins, fatty compounds and bitter and astringent principles evidenced. Finally it is concluded that this study meets the parameters established by the British Pharmacopoeia and Control Guide Medicinal Plants WHO reporting